Effect of Dietary Supplementation with L-Carnitine and Herbal Methionine in Sunflower Oil–Based Diets on Blood Biochemical Parameters, Immune Response, and Meat Quality Traits of Broiler Chickens - Mohamed, Mohammed Hasib; Rebat, Salam Ketab (American Journal of Biology and Natural Sciences, 2026)
The current study sought to determine the effects of dietary supplementation, Lcarnitine and herbal methionine on blood biochemical parameters, lipid profile, antioxidant status, hepatic enzyme activity and immune responses in broiler chicken fed on sunflower oil-based diets, as a single diet supplement or combined with other nutritional additives. Eight different treatments that were determined as diets were used and 308 broiler chicks were randomly assigned by a totally randomized experimental design. Each of the experimental diets had 5% sunflower oil and they were designed to meet the nutrient requirements provided by the). It was at 42 days of age that the blood samples were collected in order to conduct further biochemical, enzymatic, antioxidant, and immunological tests. The findings showed that L-carnitine and herbal methionine supplementation caused statistically significant (P≤0.05) increase in serum total protein and glutathione level and a concomitant decrease in glucose, total cholesterol, triglycerides, low-density lipoprotein, and very-low-density lipoprotein levels compared to the control diet. In addition, the levels of high-density lipoprotein and Newcastle disease antibody titres were significantly better in the supplemented groups, especially in chickens that were fed the combination of L-carnitine and herbal methionine diet. Though, hepatic activities of enzymes (ALT, AST, and ALP) were elevated on the basis of some treatments, the values measured fall within the normal physiological range, which shows that there were no adverse impacts on the hepatic functioning. To sum up, supplementation of L-carnitine and herbal methionine particularly in combination with each other in vivo can improve metabolic performance, antioxidant protection, lipid metabolism, and immune activity in broiler chickens fed on diets based on sunflower oil. The results validate the practicability of using such a nutritional intervention as an effective broiler system intervention.